Mauthausen und die nationalsozialistische Expansions- und Verfolgungspolitik: Europa in Mauthausen. Geschichte der Überlebenden eines nationalsozialistischen Konzentrationslagers, Band 1 - Gerhard Botz; Alexander Prenninger; Regina Fritz; Heinrich Berger (2021)
"Europe in Mauthausen" presents a comprehensive history of the survivors of a Nazi concentration camp and is based on a unique collection of 859 oral and video history interviews with former concentration camp prisoners in Europe, Israel, North and South America. This first volume focuses on methodological considerations and macro-political contexts. It shows that the National Socialist camp system was not only depending on Nazi persecution policies, but also to a large extent on the forms of occupation and collaboration in the occupied countries.